2021
DOI: 10.1038/s41390-021-01745-7
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal multidrug-resistant gram-negative infection: epidemiology, mechanisms of resistance, and management

Abstract: Infants admitted to the neonatal intensive care unit, particularly those born preterm, are at high risk for infection due to the combination of an immature immune system, prolonged hospitalization, and frequent use of invasive devices. Emerging evidence suggests that multidrug resistant gram-negative (MDR-GN) infections are increasing in neonatal settings, which directly threatens recent and ongoing advances in contemporary neonatal care. A rising prevalence of antibiotic resistance among common neonatal patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 150 publications
0
16
0
1
Order By: Relevance
“…In our study, early onset infection caused by CRKP presented in premature neonates, which is one of the main risk factors for infection caused by MDR-GN bacteria ( 21 ). Additional patient and center level risk factors for MDR infection include maternal or neonatal MDR colonization, invasive devices, history of prior unit outbreak, suboptimal infection control practices, and high antibiotic consumption ( 22 ). In hospitals where CRKP transmission was detected, maternal and infant screening for CRE carriage could lead to early detection and implementation of eradication measures to prevent new cases of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, early onset infection caused by CRKP presented in premature neonates, which is one of the main risk factors for infection caused by MDR-GN bacteria ( 21 ). Additional patient and center level risk factors for MDR infection include maternal or neonatal MDR colonization, invasive devices, history of prior unit outbreak, suboptimal infection control practices, and high antibiotic consumption ( 22 ). In hospitals where CRKP transmission was detected, maternal and infant screening for CRE carriage could lead to early detection and implementation of eradication measures to prevent new cases of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric patients are naturally vulnerable to fatal CRKP infections and get limited treatment options due to certain antibiotics with side effects, such as nephrotoxicity and ototoxicity [12]. Carbapenem resistance has been increasingly detected in paediatric wards, with high mortality reported [13–15]. In 2017, the European survey on carbapenemase-producing Enterobacteriaceae (CPE) has revealed that 37 % of the K.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal care units (NICUs) frequently experience spread of Enterobacteriaceae [5] and outbreaks involving OXA-48-producing Enterobacteriaceae strains in this setting have been reported [6][7][8]. Due to sparse colonization by anaerobic bacteria during the first weeks of life, members of the Enterobacteriaceae family establish and reach high abundance levels in the neonatal gut.…”
Section: Introductionmentioning
confidence: 99%